Building Joint Crisis Management Capacity? Comparing Civil Security Systems in 22 European Countries. Issue 1 (March 2015) - Kuipers, Sanneke; Boin, Arjen; Bossong, Raphael; Hegemann, Hendrik
<x xml:space="preserve">Abstract</x> A series of transboundary crises and disasters has increased pressure on European states to cooperate in the realm of crisis and disaster management. The European Union has taken an active role to connect national capacities of member states. Little is known, however, about the compatibilities of national civil protection systems. This article attempts to fill that void. We draw on a comparative study on 22 European states and highlight similarities as well as patterns of variation. We explore how different states define the role of government during crises and disasters; we map the administrative structures and procedures in place to provide civil security. We also assess the quality of these systems. Our findings reveal that administrative responsibilities, legal frameworks and operational practices differ markedly, as the national systems are rooted in national contexts and historical experiences. In the light of our findings, we contemplate what role the EU can play to build joint transboundary crisis management capacity.